Thermoplastic whole-core flame-retardant conveying belt and manufacturing method thereof
Through the three-layer aramid/polyester blended fabric and composite flame retardant system, the flexibility and interface bonding strength problems of the PVC whole-core flame retardant conveyor belt are solved, and high strength, wear resistance and multiple flame retardant protection are achieved, which can adapt to harsh working conditions and meet the requirements of green manufacturing.
Patent Information
- Application Number
- CN202510770972.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-10
- Publication Date
- 2025-09-12
AI Technical Summary
Existing PVC solid-core flame-retardant conveyor belts have poor flexibility and low joint strength. Rubber-based conveyor belts require high-temperature vulcanization and are at risk of failure due to migration of halogenated flame retardants. The traditional cotton/polyester canvas core has a low radial linear density, resulting in delamination and fracture, and insufficient interface bonding strength.
A three-layer aramid/polyester blended fabric is used as the core layer, impregnated with halogen-free flame-retardant polyurethane rubber, and the outer layer is covered with an ethylene-vinyl acetate copolymer-based composite layer with an intumescent flame retardant added. The wear-resistant layer is ultra-high molecular weight polyethylene, and MDI type polyurethane adhesive and silane coupling agent KH-550 are used for interface expansion. Multiple flame retardant protection and mechanical reinforcement are achieved through a low-temperature co-extrusion molding process.
It achieves improvements in high strength, wear resistance and flame retardancy, with an oxygen index of over 32% and an interlayer peel strength of 150N/cm. It can adapt to working conditions within a temperature range of -40°C to 120°C, with high production efficiency and environmental safety.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conveyor belt manufacturing, in particular to a thermoplastic solid-core flame-retardant conveyor belt and a manufacturing method thereof. Background Art
[0002] The PVC solid-core flame-retardant conveyor belts currently used extensively in coal mining and metallurgy suffer from three major technical deficiencies: First, the poor flexibility of the PVC covering results in joint strength of only 60% of the original belt, and a dynamic flex life of less than 500,000 cycles; second, rubber-based conveyor belts require a high-temperature vulcanization process, and halogenated flame retardants pose a risk of migration failure; and third, the radial linear density of traditional cotton / polyester canvas cores is generally less than 3000N / cm, making them prone to delamination and fracture under heavy loads. Aramid fiber, a new reinforcement material, has a specific strength five times that of steel wire, but the interfacial bonding strength between the pure aramid braided core and the thermoplastic covering is insufficient.
[0003] The industry urgently needs to develop new impregnation compound systems that both achieve halogen-free flame retardancy and address the hydrolysis issues of MDI adhesives in hot and humid environments. Referring to the PVG conveyor belt technology approach, while an EVA-based cover layer improves flexibility, adding more than 30 phr of conventional intumescent flame retardants can severely degrade mechanical properties. Existing impregnation processes often rely on atmospheric pressure dip coating, resulting in uneven distribution of the flame retardant in the core layer. Furthermore, the secondary vulcanization process reduces production efficiency by 40%.
[0004] While existing vacuum impregnation methods improve penetration rates, they fail to address the interfacial compatibility issues between thermoplastics and reinforcing fibers. There is an urgent need to develop a low-temperature plasticizing composite process, while simultaneously achieving key technological breakthroughs such as flame retardant microencapsulation and co-extrusion of UHMWPE wear-resistant layers. Summary of the Invention
[0005] The purpose of the present invention is to provide a thermoplastic whole-core flame-retardant conveyor belt and a manufacturing method thereof, which solves the problems of high vulcanization energy consumption of traditional flame-retardant conveyor belts and poor flexibility of PVC conveyor belts, and realizes lightweight, high-strength flame retardancy and low-temperature high-efficiency molding through a thermoplastic composite system.
[0006] The present invention achieves the above-mentioned purpose through the following technical solutions: Thermoplastic solid-core flame-retardant conveyor belt, characterized by comprising: Core material: three-layer aramid / polyester blended fabric, impregnated with halogen-free flame-retardant polyurethane rubber; Flame retardant covering layer: The outer layer is coated with ethylene-vinyl acetate copolymer based composite layer and added with intumescent flame retardant; Wear-resistant layer: surface co-extruded ultra-high molecular weight polyethylene; Adhesive layer: MDI type polyurethane adhesive, containing silane coupling agent KH-550.
[0007] During the impregnation stage, chemical bonding is achieved in the aramid / polyester blended fabric through the reaction of the MDI isocyanate (-NCO) groups in the polyurethane adhesive with the hydroxyl (-OH) groups on the fiber surface to form urethane bonds. APP (ammonium polyphosphate) decomposes upon heating to produce polyphosphoric acid and ammonia. The polyphosphoric acid promotes fiber dehydration and carbonization, forming an intumescent carbon layer. Zinc borate forms a glassy coating at high temperatures, synergistically blocking heat and oxygen. In the intumescent flame retardant system, red phosphorus generates phosphoric acid derivatives upon heating to catalyze polymer dehydration. Magnesium hydroxide decomposes to absorb heat and release water vapor to dilute the combustible gases. Melamine cyanurate interrupts the combustion chain reaction through a gaseous free radical capture mechanism. The methoxy groups of the silane coupling agent KH-550 hydrolyze to form silanols, which form Si-OC covalent bonds with the -NCO groups in the polyurethane adhesive and the surface active groups of the ultra-high molecular weight polyethylene (UHMWPE), achieving interfacial compatibilization. During melt blending, the ethylene-vinyl acetate copolymer matrix forms a physically entangled network with the flame retardant, while the UHMWPE forms a mechanically interlocked structure with the coating through molecular chain penetration.
[0008] According to a preferred embodiment of the present invention, the radial linear density of the three-layer aramid / polyester blended fabric is ≥5000 N / cm.
[0009] According to a preferred embodiment of the present invention, the halogen-free flame retardant polyurethane rubber contains 15 phr of APP and 10 phr of zinc borate.
[0010] According to a preferred embodiment of the present invention, the intumescent flame retardant consists of red phosphorus, magnesium hydroxide and melamine cyanurate.
[0011] According to a preferred embodiment of the present invention, the intumescent flame retardant consists of 5 phr of red phosphorus, 20 phr of magnesium hydroxide and 8 phr of melamine cyanurate.
[0012] According to a preferred embodiment of the present invention, the thickness of the wear-resistant layer is 0.8-1.5 mm.
[0013] According to a preferred embodiment of the present invention, the Mw of the ultra-high molecular weight polyethylene is ≥3×10 6 .
[0014] According to a preferred embodiment of the present invention, the silane coupling agent KH-550 is 1.5 phr.
[0015] The present invention also provides a method for preparing the thermoplastic solid-core flame-retardant conveyor belt, comprising the following steps: Step S1: impregnating a three-layer aramid / polyester blended fabric in a halogen-free flame-retardant polyurethane rubber compound containing 15 phr of APP and 10 phr of zinc borate for 5-8 minutes at a temperature of 50-60° C., followed by curing at 120° C. for 30 minutes; mixing an ethylene-vinyl acetate copolymer with an intumescent flame retardant consisting of 5 phr of red phosphorus, 20 phr of magnesium hydroxide, and 8 phr of melamine cyanurate, and melt-blending the mixture through a twin-screw extruder at 180-200° C. to extrude a flame-retardant layer with a thickness of 2-3 mm; Step S2: selecting ultra-high molecular weight polyethylene with Mw ≥ 3×10⁶ and extruding a 0.8-1.5 mm thick wear-resistant layer at 220-240°C using a co-extrusion device; using an MDI-type polyurethane adhesive containing 1.5 phr of silane coupling agent KH-550 to hot-press the flame-retardant cover layer and the core layer at a pressure of 0.5-0.8 MPa, maintaining the temperature at 80-100°C for 10-15 minutes; Step S3, combining the wear-resistant layer and the composite belt body through a secondary hot pressing process, controlling the hot pressing temperature to 200-220° C., the pressure to 1.0-1.2 MPa, and the time to 5-8 minutes.
[0016] According to a preferred embodiment of the present invention, the preparation method further comprises performing edge trimming and surface embossing treatment after cooling and shaping to form anti-slip lines.
[0017] The beneficial effects of the present invention are: The thermoplastic whole-core flame-retardant conveyor belt provided by the present invention has significant technical effects, which are mainly reflected in the following aspects: First, a breakthrough has been made in flame retardant performance. By adopting a three-layer aramid / polyester blended fabric as the core layer material, and impregnating it with a halogen-free flame-retardant polyurethane rubber compound containing APP and zinc borate, combined with the red phosphorus, magnesium hydroxide and melamine cyanurate intumescent flame retardant added to the outer layer of ethylene-vinyl acetate copolymer-based composite layer, a multiple flame retardant protection system is formed. This composite flame retardant structure achieves the synergistic effect of gas phase flame retardancy and condensed phase flame retardancy, so that the conveyor belt can still maintain good flame retardant performance in a high temperature environment, and the oxygen index can reach more than 32%, which can effectively prevent the spread of fire and meet the strict fire protection requirements of high-risk places such as coal mines.
[0018] Secondly, it excels in mechanical properties. The three-layer aramid / polyester blend boasts a radial linear density of ≥5000N / cm, endowing the conveyor belt with exceptionally high tensile strength and dimensional stability. The addition of an ultra-high molecular weight polyethylene (Mw ≥3×10⁶) wear-resistant layer significantly enhances surface wear resistance. The thickness of the wear-resistant layer is controlled within an optimized range of 0.8-1.5mm, ensuring both wear resistance and material waste. Testing has shown that this conveyor belt's wear resistance is over 30% higher than that of traditional rubber conveyor belts, significantly extending its service life.
[0019] Third, it offers outstanding bonding performance. Using an MDI polyurethane adhesive containing 1.5 phr of the silane coupling agent KH-550 as the adhesive layer, it achieves a strong bond between the layers through both chemical bonding and physical anchoring. This unique adhesive system achieves an interlayer peel strength exceeding 150 N / cm, effectively resolving the delamination issue of traditional conveyor belts and ensuring their structural integrity over long-term use.
[0020] The product also boasts excellent weather resistance and environmental adaptability. The halogen-free flame-retardant formula avoids the toxic gases produced by traditional halogen-containing flame retardants during combustion, making it more environmentally friendly and safer. The unique material combination ensures the conveyor belt maintains excellent flexibility and mechanical properties within a temperature range of -40°C to 120°C, adapting to a variety of harsh operating conditions. The anti-slip texture created by the embossed surface further enhances the conveyor belt's anti-slip properties, ensuring stable material transportation.
[0021] Finally, the production process is significantly innovative. Through optimized impregnation, co-extrusion, and hot-pressing lamination processes, precise control and secure bonding of each functional layer are achieved. This preparation method not only improves the consistency and stability of product performance, but also boasts high production efficiency and low energy consumption, facilitating large-scale production. The entire production process eliminates harmful emissions, meeting green manufacturing requirements. DETAILED DESCRIPTION
[0022] The following specific implementation methods are only used to further illustrate the present application and should not be understood as limiting the scope of protection of the present application. Technicians in this field may make some non-essential improvements and adjustments to the present application based on the above application content.
[0023] 1. Implementation Example 1 A three-layer aramid / polyester blended fabric (radial linear density ≥ 5000 N / cm) was impregnated with a halogen-free flame-retardant polyurethane rubber compound containing 15 phr APP and 10 phr zinc borate. The core layer 46 was formed after impregnation for 6 minutes (60°C) and curing at 120°C for 30 minutes. EVA was mixed with 5 phr red phosphorus, 20 phr magnesium hydroxide, and 8 phr melamine cyanurate, and melt-blended and extruded into a 2.5 mm flame-retardant layer through a twin-screw extruder at 190°C. The Mw = 3.5 × 10 6 The UHMWPE was co-extruded at 230℃ with a 1.2mm wear-resistant layer; an MDI polyurethane adhesive containing 1.5phr KH-550 was used, and hot pressing was performed at 0.6MPa and 90℃ for 12min (bonding strength ≥15N / mm); finally, a second hot pressing was performed at 210℃ and 1.1MPa for 6min, and after cooling, the edges were trimmed and embossed (grain depth 0.3mm).
[0024] Example 2 The core layer impregnation rubber was changed to APP 12phr and zinc borate 8phr (immersion 5min / 55℃); the flame retardant covering layer was adjusted to red phosphorus 4phr, magnesium hydroxide 18phr, and melamine cyanurate 6phr (extruded at 180℃); the adhesive layer KH-550 was reduced to 1.2phr (hot pressing at 85℃).
[0025] Example 3 The molecular weight of UHMWPE is increased to Mw=4×10 6 , the thickness of the wear-resistant layer increased to 1.5mm; the secondary hot pressing parameters were adjusted to 220℃ and 1.2MPa.
[0026] Comparative Example 1 The core layer uses pure cotton canvas instead of aramid / polyester blended fabric, impregnated with PVC rubber (containing chlorinated paraffin flame retardant); the flame retardant covering layer only adds 30phr of aluminum hydroxide.
[0027] Comparative Example 2 The flame retardant covering layer only uses 25phr of magnesium hydroxide and lacks red phosphorus and melamine cyanurate; the adhesive layer does not add KH-550 and uses ordinary polyurethane adhesive.
[0028] Comparative Example 3 Wear-resistant layer is selected Mw=1×10 6 Polyethylene (thickness 0.5mm); secondary hot pressing temperature dropped to 180℃ and pressure 0.8MPa.
[0029] 2. Performance Testing The materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested for performance according to the following method: Flame retardant performance test: According to GB / T 3685-2009 standard, the limiting oxygen index (LOI) of the sample was tested using an oxygen index meter; a vertical burning test was conducted according to GB / T 2408-2008, recording the burning time, damage length, and whether there was dripping; a cone calorimeter (ISO 5660-1) was used to measure the peak heat release rate (PHRR) and total heat release (THR). The sample size was 100mm×100mm, and the heat radiation power was 50kW / m 2 .
[0030] Mechanical Properties: Tensile strength and elongation at break were measured according to GB / T 3690-2009 (electronic tensile testing machine, 500 mm / min speed). Abrasion resistance was tested according to GB / T 9867-2008 (rotary abrader, 10 N load, 1000 revolutions). Peel strength between layers was tested according to GB / T 2791-1995 (peel angle 180°, speed 100 mm / min).
[0031] Adhesion performance test: Referring to GB / T 532-2008, the shear strength of the adhesive layer was measured using a tensile testing machine (tensile speed 50mm / min). The adhesion strength was re-measured after a damp heat aging test (70℃ / 95%RH, 168h) according to HG / T 3075-2003.
[0032] Dynamic performance test: According to MT / T 668-2019 standard, the roller dynamic bending test (curvature radius 300mm, number of cycles ≥ 50,000 times) was carried out; the fatigue testing machine was used to simulate the actual working conditions (load 80% of the rated tension, frequency 1Hz, number of cycles ≥ 2×10 6 Second-rate).
[0033] Test results: Table 1: Test results of various embodiments and comparative examples
[0034] As can be seen from Table 1, the superiority of the technical solution of the present invention is fully verified by the comparative test data of the embodiments and the comparative examples. In terms of flame retardancy, the oxygen index of Examples 1-3 all exceeds 30%, reaching the V-0 or V-1 flame retardancy standards, which is significantly better than the 26.2-28.7% oxygen index and V-2 flame retardancy of Comparative Examples 1-3. In particular, the PHRR value of Example 1 is only 112kW / m 2 , which is 43.4% lower than that of comparative example 1, proving that the synergistic effect of aramid / polyester blended fabric and composite flame retardant system is significant. Mechanical properties test shows that the tensile strength of Example 1 reaches 5280N / cm, which is 37.1% higher than that of comparative example 1, and the wear resistance index (85mm 3 ) is 147% higher than that of Comparative Example 1, thanks to the combined effects of the ultra-high molecular weight polyethylene wear-resistant layer and the reinforced core layer. In terms of bonding performance, the initial peel strength (15.3N / mm) and strength retention after wet heat aging (91.5%) of Example 1 far exceed those of Comparative Example 2 (6.2N / mm and 52.7%), confirming the reinforcing effect of KH-550 coupling agent on interfacial bonding. In the dynamic performance test, the number of dynamic bending cycles (68,000) and fatigue life (2.8×10 6times) are respectively increased by 94% and 133% compared with comparative example 1, indicating that the overall structural design has excellent durability. It is particularly noteworthy that Example 3 improves the wear resistance (78mm 3 ) and dynamic bending performance (71,000 times), while Example 2 maintained excellent overall performance by adjusting the flame retardant ratio. Comparative data showed that a traditional cotton canvas core layer (Comparative Example 1), a single flame retardant system (Comparative Example 2), and a low-molecular-weight wear-resistant layer (Comparative Example 3) all resulted in significant declines in key performance indicators, further demonstrating the necessity of the synergistic effect of the various components in the technical solution of this invention. All test data demonstrate that through innovative material combinations and process optimization, this invention achieves comprehensive improvements in flame retardancy, mechanical strength, and durability, fully meeting the requirements of industrial transportation in high-risk environments.
[0035] The above-described embodiments merely illustrate several implementations of the present invention. While the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, and all such variations and improvements fall within the scope of protection of the present invention.
Claims
1. Thermoplastic solid core flame retardant conveyor belt, characterized by: include: Core material: three-layer aramid / polyester blended fabric, impregnated with halogen-free flame-retardant polyurethane rubber; Flame retardant covering layer: The outer layer is coated with ethylene-vinyl acetate copolymer based composite layer and added with intumescent flame retardant; Wear-resistant layer: surface co-extruded ultra-high molecular weight polyethylene; Adhesive layer: MDI type polyurethane adhesive, containing silane coupling agent KH-550.
2. The thermoplastic solid-core flame-retardant conveyor belt according to claim 1, characterized in that: The radial linear density of the three-layer aramid / polyester blended fabric is ≥5000 N / cm.
3. The thermoplastic solid-core flame-retardant conveyor belt according to claim 1, characterized in that: The halogen-free flame-retardant polyurethane rubber material contains 15 phr of APP and 10 phr of zinc borate.
4. The thermoplastic solid-core flame-retardant conveyor belt according to claim 1, characterized in that: The intumescent flame retardant consists of red phosphorus, magnesium hydroxide and melamine cyanurate.
5. The thermoplastic solid-core flame-retardant conveyor belt according to claim 4, characterized in that: The intumescent flame retardant consists of 5 phr of red phosphorus, 20 phr of magnesium hydroxide and 8 phr of melamine cyanurate.
6. The thermoplastic solid-core flame-retardant conveyor belt according to claim 1, characterized in that: The thickness of the wear-resistant layer is 0.8-1.5 mm.
7. The thermoplastic solid-core flame-retardant conveyor belt according to claim 1, characterized in that: The ultra-high molecular weight polyethylene has a Mw of ≥3×10 6 .
8. The thermoplastic solid-core flame-retardant conveyor belt according to claim 1, characterized in that: The silane coupling agent KH-550 is 1.5 phr.
9. The method for preparing a thermoplastic solid-core flame-retardant conveyor belt according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step S1, dipping the three-layer aramid / polyester blended fabric into a halogen-free flame-retardant polyurethane rubber compound containing 15 phr of APP and 10 phr of zinc borate, controlling the dipping time to be 5-8 minutes and the dipping temperature to be maintained at 50-60° C., and then curing at 120° C. for 30 minutes; Ethylene-vinyl acetate copolymer is mixed with an intumescent flame retardant consisting of 5 phr of red phosphorus, 20 phr of magnesium hydroxide and 8 phr of melamine cyanurate, and melt-blended at 180-200° C. through a twin-screw extruder to extrude a flame retardant layer with a thickness of 2-3 mm; Step S2: selecting ultra-high molecular weight polyethylene with Mw ≥ 3×10⁶ and extruding a 0.8-1.5 mm thick wear-resistant layer at 220-240°C using a co-extrusion device; using an MDI-type polyurethane adhesive containing 1.5 phr of silane coupling agent KH-550 to hot-press the flame-retardant cover layer and the core layer at a pressure of 0.5-0.8 MPa, maintaining the temperature at 80-100°C for 10-15 minutes; Step S3, combining the wear-resistant layer and the composite belt body through a secondary hot pressing process, controlling the hot pressing temperature to 200-220° C., the pressure to 1.0-1.2 MPa, and the time to 5-8 minutes.
10. The preparation method according to claim 9, characterized in that The preparation method further comprises performing edge trimming and surface embossing treatment after cooling and shaping to form anti-slip lines.
Citation Information
Cited By
Rubber surface aramid fiber fabric whole core flame-retardant conveying belt and manufacturing method thereof
CN121493494A